HUBUNGAN DUKUNGAN KELUARGA DALAM PEMELIHARAAN KESEHATAN MATA DENGAN KETAJAMAN PENGLIHATAN PADA ANAK USIA SEKOLAH DASAR DI RW 10 DESA KRAMAT JEGU TAMAN SIDOARJO - damawiyah, siti; Noventi, Iis (Jurnal Ilmiah Kesehatan, 2019)
ABSTRACT: At present there is very little attention regarding visual impairment, especially in school children, whereas a poor learning environment is one of the triggers for a decrease in visual acuity in children. Myopia is one of the causes of decreased visual acuity in children, while good vision is very important in the teaching and learning process. This study aims to determine the relationship of family support in maintaining eye health with visual acuity in primary school-aged children in RW 10 Desa Kramat Jegu Taman Sidoarjo. The design of this research using a cros-sectional approach. The sample in this study were 22 elementary and sixth grade elementary school children and their mothers as many as 22 pairs. Sampling by total sampling method. Data analysis using Rank Spearman statistical test with a significance level of 5% (0.05). The results showed that of the 22 respondents most (61.18%) had good family support and from 22 respondents most (63.63%) had normal visual acuity. Spearman rank correlation test results, obtained ? = 0.032 <? = 0.05 so that H0 is rejected which means that there is a relationship between family support about maintaining eye health with visual acuity in primary school-aged children. Good family support for maintaining eye health can improve children's visual acuity. It is expected that nurses can use the results of this study as a guide in providing nursing services for patients with eye refraction disorders. Keywords: family support, visual acuity